Ecologia reprodutiva de Cardiopetalum calophyllum (Annonaceae) em fragmentos de Cerrado do Brasil Central - ELIAS, Marcos Antonio da Silva (2010)
Habitat fragmentation is one of the main causes of environmental degradation and a great threat to world biodiversity. Fragmentation can disrupt pollination processes, affecting directly or indirectly pollinators and plants. In Brazil, the Cerrado Biome has lost most part of its vegetation cover in the last four decades, becoming a highly fragmented landscape with many small fragments, several medium-size and a few continuous areas of vegetation. Those remnants have high biological diversity with high level of endemism, but very little is known about the reproductive success of their species. Cardiopetalum calophyllum Schletdl. (Annonaceae) occurs in the Cerrado of Central Brazil, has dicogamy and is pollinated by small beetle called Lobiopa insularis. The reproductive success of C. calophyllum and the abundance of its pollinator were analyzed in fragment of different size from July 2009 to January 2010. The reproductive success was estimated using fruit and seed set rates. Flowers in anthesis were collected to quantify the pollinator abundance inside them. A positive correlation between reproductive success of C. calophyllum and the fragment size was found. However, no correlation was found between pollinator abundance and fragment size. The small fragments are more isolated than the larger ones. This can decrease the pollinator dispersion and gene flow among fragments, increasing inbreeding within population of small fragments. The abundance of Lobiopa insularis seems to be more related to its generalist habits than to the fragment size. In our study, the effect of fragment size and reproductive success of C. calophyllum was stronger in fragments smaller than 10 ha. However, fragment smaller than 20 ha also showed decrease in their productive success.